2006
DOI: 10.1111/j.1600-6143.2006.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Epithelial to Mesenchymal Transition in Renal Grafts

Abstract: Epithelial-to-mesenchymal transition (EMT) of tubular epithelial cells (TECs) may participate in the pathogenesis of renal fibrosis. We performed a prospective study of EMT markers in protocol biopsies obtained 3 months after engraftment from 56 patients who received deceased donor kidneys and who had stable renal function. The presence of EMT was examined, and quantified by immunohistochemical staining for vimentin and translocation of b -catenin to the cytoplasm. EMT status was defined as the presence of EMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 33 publications
7
71
0
3
Order By: Relevance
“…Furthermore, SNAI2 expression is best explained by the association of EMT with rejection and T cell infiltration in previous studies 24,25 and the positive association with subclinical rejection and TID in this study, which was relatively low in occurrence in our study. By contrast, the significant upregulation of BCAT (MET marker/transcription factor) in TID and the negative correlation of SMAD2 expression with dual staining (EMT) argue against a role for EMT.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, SNAI2 expression is best explained by the association of EMT with rejection and T cell infiltration in previous studies 24,25 and the positive association with subclinical rejection and TID in this study, which was relatively low in occurrence in our study. By contrast, the significant upregulation of BCAT (MET marker/transcription factor) in TID and the negative correlation of SMAD2 expression with dual staining (EMT) argue against a role for EMT.…”
Section: Discussionmentioning
confidence: 59%
“…Previously in other studies, we showed that tubulointerstitial fibrosis at 3 mo is a strong prognostic entity for later graft dysfunction and TID, with acute and subclinical rejection being a strong predictor of graft fibrosis 1,2 ; however, in this study, the acute and subclinical rejection rates were relatively low as is often seen with modern immunosuppression. If EMT were driven primarily by rejection, 24,25 as suggested by some and observed in studies of clinically indicated biopsies, then this may explain our modest level of EMT by ␣-SMA or S100A4 dual staining in protocol biopsies. Another consideration is whether our biopsy time points of 1, 3, and 12 mo were too early, with ischemia-reperfusion injury possibly the cause of the early interstitial fibrosis and missed EMT-induced interstitial fibrosis at later time points.…”
Section: Discussionmentioning
confidence: 99%
“…Although no signs of tubular dedifferentiation were yet observed, cytoplasmic ␤-catenin localization has been implicated in epithelial to mesenchymal transition. 32 In addition to promoting cadherin-mediated cell junction adhesion, 33 activation of Rap1 by guanine nucleotide exchange factors (Rap1GEFs) such as C3G, PDZ-GEF, and Epac promotes clustering of integrins, thereby enhancing cell-matrix adhesion properties. 34 Similarly we found that Epac activation preserved the focal adhesion component paxillin during hypoxia ( Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…Grafts with a score $2 (10% or more of PTC cells were strongly stained by any one of the three markers) were considered EndMT-positive. This cutoff was defined before any statistical analysis, based on our experience with EMT markers, [30][31][32][33] and the level of EndMT marker expression observed in normal kidneys. The Kendall's coefficient of concordance for EndMT score between different readings by one recorder was 0.97 (P,0.001), and between two recorders was 0.86 (P=0.001).…”
Section: Immunohistochemistry For Endmt Marker Detectionmentioning
confidence: 99%